Black Bloggers and Their Varied Publics: The Everyday Politics of Black Discourse Online. (February 2018) - Steele, Catherine Knight
This article analyzes African American–oriented blogs for their potential to foster varying kinds of alternate publics while engaging in discourse that is outside what is commonly considered political communication. Bloggers and their communities use satellite and enclave spaces to explore black representation in art and media, black feminism, and class consciousness. I use critical technocultural discourse analysis to explore the affordances and constraints of blogs in creating alternate publics for African Americans online. Capitalizing on African American oral culture, black bloggers can use spaces technically accessible to the masses, yet keep discourse hidden, intentionally opting out of engagement with the dominant group. Expanding sites of inquiry and bringing a historical understanding of offline patterns of communication allow for more rich, useful, and culturally responsible research into the online communication African Americans and other marginalized communities.